A Novel Whole Blood Point-of-Care Coagulometer to Measure the Effect of Direct Oral Anticoagulants and Heparins - Ansell, Jack; Zappe, Stefan; Jiang, Xuan; Chen, Lirong; Steiner, Solomon; Laulicht, Bryan; Bakhru, Sasha (Seminars in Thrombosis and Hemostasis, 2019)
The direct oral anticoagulants (DOACs) currently require no monitoring for routine therapy of atrial fibrillation or venous thromboembolism. Measurement of activity, however, may be important in patients with major and life-threatening bleeding, patients needing emergent surgery, in reversal situations, or in patients at high risk of bleeding or thrombosis due to underlying conditions. For these patients, a widely available and rapid turnaround assay would be optimal. To date, there is no such assay available, especially for the direct factor Xa inhibitors. This report describes the performance of a new, rapid turnaround, point-of-care (PoC) assay for measuring the activity of a range of anticoagulants, including DOACs and heparins, in emergency situations and for routine measurement in high-risk patients. Perosphere Technologies' PoC coagulometer is a handheld instrument that performs individual coagulation tests on samples of fresh whole blood (∼10 µL) with clotting activated by glass contact and endpoint determination performed by infrared spectroscopy. In preclinical studies using rats anticoagulated with therapeutic doses of edoxaban or enoxaparin, the PoC coagulometer showed a strong linear correlation between pharmacokinetic parameters and clotting time with edoxaban (r2 = 0.994) and with enoxaparin (r2 = 0.967). These preclinical results suggest that this PoC coagulometer would be ideal to assess the pharmacodynamic effects of anticoagulants and their reversal agents. The PoC bedside instrument delivers results within minutes and requires no more than a drop of whole blood. Studies are underway to confirm these results in humans and to further characterize the performance of the instrument.
Keywords: coagulometer; point-of-care; anticoagulants; direct oral anticoagulants